Biomarkers in Routine Heart Failure Clinical Care - Sunil K Nadar (Radcliffe Medical Media, 2019)
Heart failure is a clinical condition with complex pathophysiology that involves many different processes. Diagnosis is often difficult in patients presenting for the first time with breathlessness. Many biomarkers have been identified that are elevated in heart failure and their role in assessing prognosis has also been investigated. However, at present the natriuretic peptides appear to be the gold standard biomarker against which the other biomarkers are compared. In this review we will examine the evidence behind the other biomarkers for use in heart failure patients and the current guidelines for their use.